Qaraqalpaq tilinde ólshem atamalarÍnÍń FRAZEOLOGIYaLÍQ SÓZ DIZBEKLERI ARQALÍ AŃLATÍLÍWÍ - Bekniyazov, Q. (SCIENCE and SOCIETY, 2025)
The article analyzes phraseological units related to measurement terms in the Karakalpak language. It is scientifically proven that phraseological units connected with measurement terminology are linguocultural units. Scientific conclusions are given regarding the linguistic functions of phraseological units. It is noted that words related to measurement terminology have been used in our language since ancient times, and such words are also widely found within phraseological units in the Karakalpak language. In addition, the formation and integration into our language of words and phraseological expressions denoting time, weight, length, space, and scale in the lexical composition of the Karakalpak language are thoroughly analyzed.